Transformation of the Constitutional Identity in South Africa after the Fall of Apartheid - Wawrzyński Patryk (BIALOSTOCKIE STUDIA PRAWNICZE, 2024)
This article investigates the designed transformation of South African political identity and its constitutional framework as a core aspect of the democratization of South Africa. It compares the racist and exclusive identity of the apartheid state with a redesigned identity of an inclusive and open ‘Rainbow Nation’, a concept coined by Archbishop Desmond Tutu and spearheaded by Nelson R. Mandela along with the African National Congress. The study considers changes in the legal framework of identity politics, from the Republic of South Africa Constitution Act of 1983 (and the previous apartheid republican Constitution of 1961) through the interim democratic Constitution of 1993 to the Constitution of the Republic of South Africa of 1996. It discusses the possible significance of the 18 amendments to the act regarding South Africans’ social and political identities, and establishes a complex and detailed portrayal of the republic’s legal framework of identity politics. The study combines legal, political, and cultural analysis of the role of law in formatting social and political identities, using survey results to test its impact on society. In conclusion, the paper considers the effects of post-apartheid identity transformation in South Africa.